Daily rhythm of melanopsin-expressing cells in the mouse retina - Gonzalez-Menend, Irene; Contreras, Felipe; Cernuda-Cernuda, Rafael; Garcia-Fernandez, Jose M. (Frontiers in Cellular Neuroscience, 2009)
In addition to some other functions, melanopsin-expressing retinal ganglion cells (RGCs) constitute the principal mediators of the circadian photoentrainment, a process by which the suprachiasmatic nucleus (the central clock of mammals), adjusts daily to the external day/night cycle. In the present study these RGCs were immunohistochemically labelled using a specific polyclonal antiserum raised against mouse melanopsin. A daily oscillation in the number of immunostained cells was detected in mice kept under a light / dark (LD) cycle. One hour before the lights were on (i.e., the end of the night period) the highest number of immunopositive cells was detected while the lowest was seen four hours later (i.e., within the first hours of the light period). This finding suggests that some of the melanopsin-expressing RGCs “turn on” and “off” during the day/night cycle. We have also detected that these daily variations already occur in the early postnatal development, when the rod/cone photoreceptor system is not yet functional. Two main melanopsin-expressing cell subpopulations could be found within the retina: M1 cells showed robust dendritic arborization within the OFF sublamina of the inner plexiform layer (IPL), whilst M2 cells had fine dendritic processes within the ON sublamina of the IPL. These two cell subpopulations also showed different daily oscillations throughout the LD cycle. In order to find out whether or not the melanopsin rhythm was endogenous, other mice were maintained in constant darkness for six days. Under these conditions, no defined rhythm was detected, which suggests that the daily oscillation detected either is light-dependent or is gradually lost under constant conditions. This is the first study to analyze immunohistochemically the daily oscillation of the number of melanopsin-expressing cells in the mouse retina.